2023
DOI: 10.3389/fagro.2023.1215441
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide development of agronomic management practices for quinoa cultivation: a systematic review

Abstract: Quinoa (Chenopodium quinoa Wild.) is a drought and salinity-tolerant crop that originated in the Andes over 7000 years ago. It is adapted to different agroecological areas and can be grown from sea level to an altitude of 4000 m. The outstanding nutritional status of quinoa, with its high content of proteins, vitamins, and minerals, makes it a promising crop able to combat hunger and malnutrition in different countries in the 21st century. Quinoa cultivation has expanded from South America to Africa, Europe, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…There has been a remarkable increase in the cultivated area of quinoa in the last few years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), especially in the Bolivian region, with increases from 35,690 to 64,789 ha −1 , and in Peru, with increases from 27,578 to 37,625 ha −1 . The major importers of their harvests are the United States of America (53%), Canada (15%), France (8%), Germany (4%), the Netherlands (4%), Australia (3%), and the UK (2%) [10].…”
Section: Quinoa's Superiority Over Other Cerealsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a remarkable increase in the cultivated area of quinoa in the last few years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), especially in the Bolivian region, with increases from 35,690 to 64,789 ha −1 , and in Peru, with increases from 27,578 to 37,625 ha −1 . The major importers of their harvests are the United States of America (53%), Canada (15%), France (8%), Germany (4%), the Netherlands (4%), Australia (3%), and the UK (2%) [10].…”
Section: Quinoa's Superiority Over Other Cerealsmentioning
confidence: 99%
“…Recently, the yield potential of seven quinoa genotypes was explored in the hot-arid regions of North Africa, and it was found that some genotypes are high-yielding and have better grain quality with short harvesting maturity [62]. Despite the wider adaptability of quinoa, its yield is quite varied, from 108 kg ha −1 to 9667 kg ha −1 around the world [35].…”
Section: Adaptability To Agro-ecological Extremesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, quinoa positively responded to the addition of goat manure up to 4 t ha − 1 (González et al 2023). Although some studies have reported the positive effect of soil organic fertilizers on quinoa productivity (Taaime et al 2023), no research has addressed the residual effect of such fertilizers on quinoa productivity and nutrient uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Both species have been used since pre-agricultural times, and have long been cultivated following ancestral, sustainable methods that enable production in conditions of high altitude, drought, salinity and frost and which hold valuable lessons for the current climate emergency [33][34][35].…”
Section: Introductionmentioning
confidence: 99%